481 Impact of COVID-19 on Cancer Patients Receiving Immune Checkpoint Inhibitors. (10th December 2020) - Tyan, Kevin; Bui, Ai-Tram; Giobbie-Hurder, Anita; Klein, Isaac; Manos, Michael; Zubiri, Leyre; Reynolds, Kerry; Grover, Shilpa; Weinhouse, Gerald; Ott, Patrick; LeBoeuf, Nicole; Rahma, Osama
Abstract : Background: There are conflicting data regarding the vulnerability of cancer patients receiving immune checkpoint inhibitors (ICIs) to COVID-19 infection. 1–3 In addition, immune-related adverse events (irAEs) driven in part by cytokine dysregulation could parallel the cytokine storm implicated in COVID-19. We sought to evaluate the impact of COVID-19 infection on irAEs and mortality in cancer patients receiving ICIs. Methods: We performed a retrospective matched cohort study of 25 patients receiving ICIs within one year of a confirmed COVID-19 diagnosis between March 20, 2020 and June 3, 2020 at the Dana-Farber Cancer Institute/Mass General Brigham network. Cases were matched 1:1 with controls without ICI use based on age, sex, and use of non-ICI anti-cancer therapy within 6 months prior to COVID-19 diagnosis. The primary outcome was death due to COVID-19, and potential covariates (patient comorbidities, concomitant medications, ICI therapy, other anti-cancer therapy) were explored using multivariable logistic regression models. Results: We reviewed the records of 611 patients with prior ICI use who were evaluated at our institutions. The final study population included 25 patients who tested positive for COVID-19. The median age was 72 years (range 45–83) and 11 patients (44%) were female (table 1 ). Seven of 25 (28%) patients on ICIs died from COVID-19 compared to 9 of 25 (36%) controls (figure 1 ). In multivariable analysis, determinants of mortality included age (OR 1.14, 95% CI 1.03–1.27) and chronic obstructive pulmonary disease (OR 12.26, 95% CI 1.76–85.14), while concomitant statin use was protective against mortality (OR 0.08, 95% CI 0.01–0.63). After adjusting for age, sex, and anti-cancer therapy, ICI use was not associated with increased risk for COVID-19 death (OR 0.36, 95% CI 0.07–1.87, figure 2 ). Two patients experienced persistent irAEs (hypophysitis) and one patient had new onset irAE (hypothyroidism) during their COVID-19 course. Patients with ICI use presented with significantly higher platelet (p = 0.017) and D-dimer (p = 0.037) levels compared to controls (figure 3 A). Elevated troponin levels (p = 0.01) were associated with COVID-19 death in patients using ICI but not in controls (figure 3 B). Conclusions: In our study, ICI use was not associated with increased risk of COVID-19 related death. We observed low rates of new or persistent irAEs within our small sample. The potential protective effect of statin therapy and predictive role of laboratory biomarkers warrants further investigation. Our findings are promising for the continuation of immunotherapy in cancer patients with COVID-19. Acknowledgements: K.T. and A.N.B. contributed equally. N.R.L. and O.E.R. contributed equally.The authors would like to acknowledge the DFCI Oncology Data Retrieval System (OncDRS) for the aggregation, management, and delivery of the clinical and operational research data used in this project. The content is solely the responsibility of the authors. Ethics Approval: This project was approved by the Partners Healthcare Institutional Review Board (#2020P000851). References: Robilotti EV, Babady NE, Mead PA, et al. Determinants of COVID-19 disease severity in patients with cancer. Nature Medicine 2020. In press. Luo J, Rizvi H, Egger JV, Preeshagul IR, Wolchok JD, Hellmann MD. Impact of PD-1 blockade on severity of COVID-19 in patients with lung cancers. Cancer Discov 2020. In press. Lee LYW, Cazier JB, Starkey T, Turnbull CD, Kerr R, Middleton G. COVID-19 mortality in patients with cancer on chemotherapy or other anticancer treatments: a prospective cohort study. Lancet 2020;395(10241):1919–1926.